Subject‐specific optimization of background suppression for arterial spin labeling magnetic resonance imaging using a feedback loop on the scanner. (9th May 2022) - Koolstra, Kirsten; Staring, Marius; de Bruin, Paul; van Osch, Matthias J. P.
Abstract : Background suppression (BGS) in arterial spin labeling (ASL) magnetic resonance imaging leads to a higher temporal signal‐to‐noise ratio (tSNR) of the perfusion images compared with ASL without BGS. The performance of the BGS, however, depends on the tissue relaxation times and on inhomogeneities of the scanner's magnetic fields, which differ between subjects and are unknown at the moment of scanning. Therefore, we developed a feedback loop (FBL) mechanism that optimizes the BGS for each subject in the scanner during acquisition. We implemented the FBL for 2D pseudo‐continuous ASL scans with an echo‐planar imaging readout. After each dynamic scan, the acquired ASL images were automatically sent to an external computer and processed with a Python processing tool. Inversion times were optimized on the fly using 80 iterations of the Nelder–Mead method, by minimizing the signal intensity in the label image while maximizing the signal intensity in the perfusion image. The performance of this method was first tested in a four‐component phantom. The regularization parameter was then tuned in six healthy subjects (three males, three females, age 24–62 years) and set as λ = 4 for all other experiments. The resulting ASL images, perfusion images, and tSNR maps obtained from the last 20 iterations of the FBL scan were compared with those obtained without BGS and with standard BGS in 12 healthy volunteers (five males, seven females, age 24–62 years) (including the six volunteers used for tuning of λ). The FBL resulted in perfusion images with a statistically significantly higher tSNR (2.20) compared with standard BGS (1.96) ( p < 5 x 10 − 3, two‐sided paired t‐test). Minimizing signal in the label image furthermore resulted in control images, from which approximate changes in perfusion signal can directly be appreciated. This could be relevant to ASL applications that require a high temporal resolution. Future work is needed to minimize the number of initial acquisitions during which the performance of BGS is reduced compared with standard BGS, and to extend the technique to 3D ASL. Abstract : Background suppression for arterial spin labeling MRI was optimized in a subject‐specific manner using a feedback loop on the scanner. This feedback loop adjusts the inversion timings during acquisition following the Nelder–Mead optimization scheme. This resulted in perfusion images with a statistically significantly higher tSNR compared with standard background suppression.